Hepatoprotective Effect of Cynodon dactylon on CCI4 Induced Experimental Mice (Journal of Bio-Science, 2011)
Context: Medicinal plants having diverse pharmacological properties including cytotoxic and cancer chemopreventive effects can be developed as novel drugs for cancer chemoprevention. One of the best approaches in search for anticancer agents from plant resources is the selection of plants based ethnomedical leads and testing the selected plants efficacy and safety in light of modern science.Objectives: The present study aims in assessing the hepatoprotective activity of protein fraction of Cynodon dactylon on CCl4 induced mice.Materials and Methods: Fresh leaves were homogenized with phosphate buffered saline (PBS) at 4°C to obtain 20 % homogenate. The supernatant obtained was used for the ammonium sulphate fractionation. Hepatoprotective role was evaluated in the liver of mice administered with and without protein fraction. Paraffin oil and PBS serves as the vehicle control for Silymarin and protein fraction respectively. Silymarin was used as the standard antioxidant. CCl4 acts as a hepatotoxin. The activity of enzymic antioxidants Catalase (CAT), Superoxide dismutase (SOD) and Peroxidase (Px) were determined in the liver homogenate of the control and experimental mice. The levels of these antioxidants were also assessed in the liver homogenate of the control and experimental mice.Results: The protein fraction of Cynodon dactylon had significant hepatoprotective potential by enhancing the activities of enzymic antioxidants, increasing the levels of non enzymic antioxidants, marker enzymes and antilipid peroxidative role by decreasing the lipid peroxide levels. These effects were found to be more significant than that of silymarin, the standard antioxidant and the CCl4 the hepatotoxin. Administration of Cynodon dactylon plus CCl4 significantly decreases the levels of liver marker enzymes, hepatic enzymic and non enzymic antioxidants. The observed increased levels of lipid peroxides and decreased levels of enzymic and non enzymic antioxidants are the indications of liver damage due to high oxidative stress in CCl4 induced mice when compared to the respective vehicle controls.Conclusion: The findings of the present study revealed that the Cynodon dactylon had the potent hepatoprotective activity due to its antioxidant property against CCl4 induced liver damage in mice. Key words: Protein fraction; Cynodon dactylon; enzymic antioxidants; lipid peroxides; marker enzymes; CCl4.DOI: 10.3329/jbs.v17i0.7096J. bio-sci. 17: 27-34, 2009